2017
DOI: 10.3390/md15100306
|View full text |Cite
|
Sign up to set email alerts
|

Production of Fish Protein Hydrolysates from Scyliorhinus canicula Discards with Antihypertensive and Antioxidant Activities by Enzymatic Hydrolysis and Mathematical Optimization Using Response Surface Methodology

Abstract: Fish discards are of major concern in new EU policies. Alternatives for the management of the new biomass that has to be landed is compulsory. The production of bioactive compounds from fish protein hydrolysates (FPH) has been explored in recent years. However, the viability of Scyliorhinus canicula discards, which might account for up to 90–100% of captures in mixed trawler, gillnet, and longline industrial fisheries, to produce FPH from the muscle with bioactivities has still not been studied in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 38 publications
1
45
0
4
Order By: Relevance
“…Optimization of salmonid heads hydrolysis was studied according to the factorial designs summarized in Table S1 (supplementary material) using a pH-stat system (100 mL reactor). Alcalase 2.4 L was chosen as biocatalyst due to its excellent capacity of proteolysis when it was applied to several marine substrates as squid pens, fish cartilages, crustacean shells, and other fish tissues and by-products [19][20][21][22]. A two-variable factorial design was executed in anticipation that no interactions among pH, T, r (S:L), and enzyme concentration were expected as it was reported by Liaset et al [3].…”
Section: Optimization Of Salmonid By-products Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of salmonid heads hydrolysis was studied according to the factorial designs summarized in Table S1 (supplementary material) using a pH-stat system (100 mL reactor). Alcalase 2.4 L was chosen as biocatalyst due to its excellent capacity of proteolysis when it was applied to several marine substrates as squid pens, fish cartilages, crustacean shells, and other fish tissues and by-products [19][20][21][22]. A two-variable factorial design was executed in anticipation that no interactions among pH, T, r (S:L), and enzyme concentration were expected as it was reported by Liaset et al [3].…”
Section: Optimization Of Salmonid By-products Hydrolysismentioning
confidence: 99%
“…The hydrolysis degree (H, as %) was calculated according to the pH-Stat method [48] and the mathematical models previously reported [22]. The time course of H were fitted to the Weibull equation [27]:…”
Section: Production Of Enzymatic Hydrolysates From Salmonids By-productsmentioning
confidence: 99%
“…At the end of the hydrolysis (6 h), samples were centrifuged (6000 g for 20 min) and liquid fractions (hydrolysates) stored at -18ºC until analysis. Degree of hydrolysis (H, as %) was quantified following the pH-Stat method (Adler-Nissen, 1986) and equations previously described (Vázquez, Blanco, Massa, Amado, & Pérez-Martín, 2017). Hydrolysis kinetics were finally modelled by Weibull equation (Vázquez et al, 2017):…”
Section: Proteolysis Of C Monstrosa Cartilagementioning
confidence: 99%
“…has generally led to high hydrolysis values and complete digestion of solid cartilage. In the present study the enzyme selected is Esperase, a serine-type endoprotease which has shown high proteolytic activity on fish and cephalopod waste substrates (Akagündüz et al, 2014;Vázquez et al, 2017). Table for the enzymatic hydrolysis of C. monstrosa cartilage.…”
Section: Hydrolysis Of C Monstrosa Cartilage By Esperasementioning
confidence: 99%
“…Every year, the seafood processing industry discards a large amount of by-products, including viscera, shells, heads, squid pens, fins, and bones, even though they could be recycled to produce bioactive compounds like gelatin [1][2][3][4], enzymes [4][5][6][7][8][9][10][11][12][13][14][15][16][17], chitin [8,[18][19][20][21][22][23][24][25][26], chitin oligomers [7,11,12], α-glucosidase inhibitors (aGI) [27][28][29][30][31], carotenoids [32,33], and bioactive peptides [34][35][36][37][38][39][40]. Consequently, much research has gone into converting these by-products into bioactive products that have potential applications in biotechnological, agricultural, nutritional, pharmaceutical, and biomedical industries [1,…”
Section: Introductionmentioning
confidence: 99%